Освоєння міфологічного дискурсу дитячою міською субкультурою: медіумічні практики - Буйських, Ю. (Народна творчість та етнологія, 2014)
Дитячі медіумічні практики, що побутують у місті, є одним з найяскравіше виражених способів освоєння дитячою субкультурою міфологічного дискурсу. У статті висвітлено явище «викликання» надприродних істот у дитячій міській субкультурі кінця 80-х – середини 90-х років XX ст. (на прикладі української міської традиції). Воно розглядається як таке, що перебуває на межі гри, міфології, магії. Запропоновано типологію медіумічних практик, розглянуто їхній персонажний склад, проаналізовано функції. Children’s spiritual intermediary practice existing in the cities is one of the most strong and expressive ways of mastering the mythological discourse by children’s subculture. The article enlightens the cultural appearance of the evocation of supernatural entities in urban children’s subculture in the late 1980s to mid-1990s (by way of example of Ukrainian urban tradition). The phenomenon is considered to be the closest to the point where game, mythology, and magic converge, featuring elements of each of them. The typology of various spiritual intermediary practices has been proposed, and the composition of those characters who act through the evocations has been examined. The main functions of the practices have been analyzed as well.